2021
DOI: 10.1097/cce.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

PHarmacist Avoidance or Reductions in Medical Costs in CRITically Ill Adults: PHARM-CRIT Study

Abstract: OBJECTIVES: To comprehensively classify interventions performed by ICU clinical pharmacists and quantify cost avoidance generated through their accepted interventions. DESIGN: A multicenter, prospective, observational study was performed between August 2018 and January 2019. SETTING: Community hospitals and academic medical centers in the United States. PARTICIPANTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 34 publications
1
70
0
Order By: Relevance
“…While research demonstrating the benefit of clinical pharmacy services has been conducted for decades, the problem remains that health care is driven by revenue generation. The presence of clinical pharmacists undoubtedly leads to a high level of cost avoidance 3,6,20 . However, this does little to generate actual revenue, as clinical pharmacy services are not typically reimbursable.…”
Section: Barriers To Retention and Contributors To Attritionmentioning
confidence: 99%
See 4 more Smart Citations
“…While research demonstrating the benefit of clinical pharmacy services has been conducted for decades, the problem remains that health care is driven by revenue generation. The presence of clinical pharmacists undoubtedly leads to a high level of cost avoidance 3,6,20 . However, this does little to generate actual revenue, as clinical pharmacy services are not typically reimbursable.…”
Section: Barriers To Retention and Contributors To Attritionmentioning
confidence: 99%
“…In contrast, clinical pharmacists are typically responsible for the care of entire units or medical services and have fewer opportunities to secure protected time and clinical career advancement. Indeed, a recent study of intensive care unit pharmacists demonstrated that nearly a third of participants covered at least two services, corresponding to a median of 21 patients (compared with 13 patients for those covering one service) 3 . Beyond bedside care, clinical pharmacist responsibilities can include the following: both prospective and retrospective order verification, precepting trainees (eg, pharmacy residents and students), hospital or clinic committee participation, research and scholarship, and involvement in national and local organization leadership, guideline, protocol, and medication use processes development, among other unit and pharmacist‐specific roles 4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations